Living standards, poverty and inequality in the UK: 2022 - Jonathan Cribb; Tom Waters; Thomas Wernham; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2022)
This report examines how material living standards - most commonly measured by households' incomes - have changed for different groups in the UK, and the consequences that these changes have for income inequality and for measures of deprivation and poverty. This is the 22nd annual report published by IFS authors on living standards, poverty and inequality in the UK since the annual reports started in 2001. In this report, we focus on two particular issues. First, we look at how the distribution of household income changed during the first year of the COVID-19 pandemic. Second, we use pre-pandemic data on child poverty and material deprivation to examine the situation facing poor families with children prior to the pandemic.
Keywords: 330